PERILAKU APARAT DESA DALAM PELAKSANAAN TUGAS MENGHADAPI PANDEMI COVID -19 DI DESA KOLONGAN KECAMATAN KALAWAT KABUPATEN MINAHASA UTARA - BOKANG, GEOVANA GABRIELA; POSUMAH, JOHNNY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2021)
In preventing COVID-19 in villages and residential areas, the role of the village government is verynecessary as the main key that can be the main key to break the chain of spreading the Covid-19 virus inthe community. Information control and the efforts made by the government are very much needed in thesituation of handling the spread of the Covid-19 virus that occurred in Kolongan Village, Kalawat District,North Minahasa Regency. The efforts made by the village government are aimed at breaking the chain ofthe spread of the virus. However, the efforts that have been made have not obtained maximum results inaccordance with what was expected. Therefore, this study is proposed to answer questions about theBehavior of Village Officials in Facing the Covid-19 Pandemic in Kolongan Village, Kalawat District,North Minahasa Regency. In this study using the behavioral theory of Benjamin Bloom, in theory Bloomsaid that human behavior can be seen from three domains or areas that can be used as benchmarks.Cognitive or knowledge. It is the result of knowing and is formed after someone senses a certain object.Affective or attitude. Is a reaction or response that is still closed to a stimulus or object. Psychomotor oraction. Are all human activities or activities, both those that can be observed directly and those that cannotbe observed from the outside. This study uses qualitative research methods by conducting data collectionmethods by interviewing 10 informants in direct observation, looking for documents related to researchassisted by recording devices and writing instruments. The results of this study indicate that the Behaviorof Village Officials in Facing the Covid-19 Pandemic in Kolongan Village, Kalawat District, NorthMinahasa Regency has not achieved maximum results.Keywords : Behavior of Village Officials, Covid-19 Pandemic